The Effect of I Love You Massage on Reducing Contraception in Infants Aged 6-12 Months at The South Bulango Health Center - Sri Maryati Ahmad; Sulistiyah Sulistiyah (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Constipation is a common health problem among infants aged 6–12 months, which can lead to discomfort, feeding difficulties, and reduced quality of life. Non-pharmacological interventions, such as the I Love You (ILU) massage, have been suggested to improve bowel regularity and reduce gastrointestinal discomfort in infants. Objective: This study aimed to examine the effect of ILU massage on reducing constipation in infants aged 6–12 months at the South Bulango Health Center. Methods: A pre-experimental design with a one-group pretest–posttest approach was applied. Data on bowel movement frequency, stool consistency, and abdominal discomfort were collected before and after the intervention using structured observation sheets and caregiver questionnaires. Data analysis was performed using paired t-tests, with statistical significance set at p < 0.05. Results: The results showed a significant increase in bowel movement frequency from 2.1 ± 0.8 times per week before the intervention to 4.5 ± 1.0 times per week after the intervention (p = 0.000). Stool consistency improved from a mean Bristol score of 2.0 ± 0.6 to 4.0 ± 0.7 (p = 0.000), and abdominal discomfort decreased from 3.5 ± 1.0 to 1.2 ± 0.8 (p = 0.000). These findings indicate that ILU massage effectively alleviates constipation symptoms in infants. Conclusion: ILU massage is an effective, safe, and non-invasive method to reduce constipation in infants aged 6–12 months. Involving caregivers in the intervention enhances its effectiveness and supports parent–child bonding, making it suitable for integration into routine infant care at community health centers.